2020
DOI: 10.1042/bcj20200426
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome a promising target for management of respiratory diseases

Abstract: The intestinal microbial flora has risen to be one of the important etiological factors in the development of diseases like colorectal cancer, obesity, diabetes, inflammatory bowel disease, anxiety and Parkinson's. The emergence of the association between bacterial flora and lungs led to the discovery of the gut–lung axis. Dysbiosis of several species of colonic bacteria such as Firmicutes and Bacteroidetes and transfer of these bacteria from gut to lungs via lymphatic and systemic circulation are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 101 publications
0
28
0
Order By: Relevance
“…For example, detection of Staphyloccocus overgrowth in the nose and lungs and Haemophilus depletion in the oropharynx and lungs would provide more direct evidence for the assertion that the supraglottic microbiome protects the lungs from nasal, skin, and environmental microbes. In addition, strategies to characterize gut-lung cross-talk may further elucidate factors influencing the pulmonary microbiome ( 33 , 34 ). Ultimately, strategies to modulate the lung microbiome to improve pulmonary health remain in development and include investigation of both ingested and inhaled probiotics and other microbial metabolites ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, detection of Staphyloccocus overgrowth in the nose and lungs and Haemophilus depletion in the oropharynx and lungs would provide more direct evidence for the assertion that the supraglottic microbiome protects the lungs from nasal, skin, and environmental microbes. In addition, strategies to characterize gut-lung cross-talk may further elucidate factors influencing the pulmonary microbiome ( 33 , 34 ). Ultimately, strategies to modulate the lung microbiome to improve pulmonary health remain in development and include investigation of both ingested and inhaled probiotics and other microbial metabolites ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that alteration of the gut or fecal microbiome is prominent not only when a single antibiotic is used but also when a combination therapy is used such as gentamicin-ampicillin and ciprofloxacinmetronidazole (Ferrer et al, 2014, Heinsen et al, 2015, Koido et al, 2014. Thus, antibiotic treatment for pneumonia can affect the abundance and diversity of the gut microbiome, and dysbiosis of the colonic microbiome influencing disparate sites via the gut-respiratory tract axis through lymphatic and systemic circulation may impact secondary tissue and immune homeostasis of the airway (Schuijt et al, 2016, Trivedi andBarve, 2020). This phenomenon can serve as microbiological evidence that can be associated with the development of diseases such as COM and chronic rhinosinusitis after pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…There may be two main routes for transfer of intestinal bacteria to the lung tissue: the first is intestinal bacteria or bacterial components enter into the circulation through the mesenteric lymphatic system and then reach the lung tissue ( 162 164 ); the second is the migration of intestinal bacteria or bacterial components to the lung tissue through microbreathing and oropharyngeal reflux ( 165 , 166 ). Therefore, Lactobacillus or components of Lactobacillus in the intestine may be directly transferred to lung tissue and thus modulate lung immunity.…”
Section: Potential Mechanism Of Probiotic Lactobacillus ...mentioning
confidence: 99%